2022
DOI: 10.3390/s22062418
|View full text |Cite
|
Sign up to set email alerts
|

Microservice Security Framework for IoT by Mimic Defense Mechanism

Abstract: Containers and microservices have become the most popular method for hosting IoT applications in cloud servers. However, one major security issue of this method is that if a container image contains software with security vulnerabilities, the associated microservices also become vulnerable at run-time. Existing works attempted to reduce this risk with vulnerability-scanning tools. They, however, demand an up-to-date database and may not work with unpublished vulnerabilities. In this paper, we propose a novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Thus, the incorrectly patched software containers may determine vulnerable microservices. Ying et al [46] proposed a system to enhance container-side security models, which concern unknown attack patterns related to a "mimic defence network". Thus, a set of resources regarding attack pattern images was created.…”
Section: Software Platformsmentioning
confidence: 99%
“…Thus, the incorrectly patched software containers may determine vulnerable microservices. Ying et al [46] proposed a system to enhance container-side security models, which concern unknown attack patterns related to a "mimic defence network". Thus, a set of resources regarding attack pattern images was created.…”
Section: Software Platformsmentioning
confidence: 99%
“…Although some existing contributions aim to reduce the implied security risks using vulnerability detection tools, outdated databases prevent a proper detection process to occur on newly published vulnerabilities. The research work reported in [ 47 ] describes a system intended to enhance container-side security models, which targets unknown attack patterns using a "mimic defence network". More precisely, a resource pool that contains attack pattern images is built.…”
Section: Relevant Existing Contributionsmentioning
confidence: 99%
“…Mimic defense 24 The scheme is based on the cloud with a container environment using Kubernetes native environment.…”
Section: Misery Diagraph 10mentioning
confidence: 99%
“…Similarly, it is displayed that proxy servers can be focused on specific proxy‐related attacks, that is, proxy harvesting, which needs nonstop remapping to interrupt the attacks 23 . The authors in Reference 24 proposed a mechanism for the enhancement of microservices security using the mimic defensive framework based on the MTD mechanism. They created a resource pool with different images and observed the inconsistency in the execution outcomes.…”
Section: Related Workmentioning
confidence: 99%